Estimation of the size of hillocks caused by swift heavy ions - Аралбаева, Г.М. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
The temperature dependence of the height of the hillocks on the surface of T iO2 crystals was investigated. Irradiation was carried out on a single crystal rutile crystal of T iO2 with an irradiation surface [110] using xenon ions with an energy of 220 MeV to a fluence of 5 ∗ 1010 ион/см 2 . Irradiation was carried out at temperatures of 80 K and 1000 K. Experimentally, it was found that the average height of hillock increases with irradiation temperature. The changes in the height of the hillocks depending on the irradiation temperature were estimated within the framework of the thermal peak model. The role of material viscosity in the formation of hillocks is determined by comparing the two approaches based on the Bernoulli law and the Navier-Stokes equations.